Nepal Development Update, December 2019 : Envisioning a Future Data Ecosystem in Federal Nepal - World Bank (World Bank, Kathmandu, 2019)
Economic growth in Nepal remained robust, reaching 7.1 percent in FY2019. This is in contrast with past growth that averaged 4.1 percent a year between FY2007 and FY2016. The service sector accounted for 57 percent of the growth, and the agriculture sector contributed an additional 24 percent. Higher remittance inflows and a surge in tourist arrivals translated into higher growth in retail trade, real estate, transport, and hotel and restaurant services. Good monsoons and increased commercialization coupled with improved availability of fertilizers, seeds, and irrigation facilities contributed to higher paddy, maize, and wheat production. Higher remittances also supported increased private consumption, while private investment expanded because of regular electricity supply and greater political and policy stability. However, public investment contracted as post-earthquake housing reconstruction slowed and national pride projects like Melamchi water supply and Upper Tamakoshi hydroelectric were further delayed. Net exports continued to underperform.